Total Aqueous Synthesis of Au@Cu2−xS Core–Shell Nanoparticles for In Vitro and In Vivo SERS/PA Imaging‐Guided Photothermal Cancer Therapy. Issue 2 (7th December 2018) - Lv, Qian; Min, Huan; Duan, Dong‐Ban; Fang, Wei; Pan, Gui‐Ming; Shen, Ai‐Guo; Wang, Qu‐Quan; Nie, Guangjun; Hu, Ji‐Ming
Abstract: Both accurate tumor navigation and nanostructures with high photothermal (PT) conversion efficiency are important but remain challenging to achieve in current biomedical applications. This study reports an anion exchange‐based facile and green approach for synthesizing Au@Cu2− x S core–shell nanoparticles (NPs) in an aqueous system. In addition to the PT effect of the suggested NPs, the surface‐enhanced Raman scattering (SERS) is also significantly improved due to the tailored localized surface plasmon resonance coupling between the Au metal core and the Cu2− x S semiconductor shell. Using an epitaxial strategy, Au@Cu2 O NPs are first obtained by the in situ reduction of cupric hydroxide on a cresyl violet acetate‐coated Au core; then, Au@Cu2− x S NPs are obtained via anion exchange between the S 2− and Cu2 O shell. Both the Cu/S atomic ratio and the Cu2− x S shell thickness can be adjusted conveniently. Hence, the ideal integration of the plasmonic Au core and Cu2− x S shell into a single unit is conducive not only to highly efficient PT conversion but also to the construction of a SERS‐based navigator. This new type of SERS‐guided NP, with enhanced photoacoustic signals, is an important candidate for both accurate tumor navigation and nondestructive PT treatment guided in vivo by two modes of optical imaging. Abstract : The Au@Cu2− x S core–shell nanoparticles (NPs) are constructed in a facile and green method under aqueous phase. The ratio of Cu/S and the thickness of Cu2− x S shell can be adjusted flexibly to achieve the enhanced surface‐enhanced Raman scattering (SERS) and photothermal effects. With the SERS and photoacoustic imaging, the NPs are used for accurate tumor location and efficient tumor inhibition in vivo.